Out-of-Pocket Expenditure on Medical Services Among Older Adults: A Longitudinal Analysis - Tur-Sinai, Aviad (Frontiers in Public Health, 2022)
The upturn in life expectancy and its consequence, population aging, are challenging labor, pension, and social-security systems throughout the developed world. The focal aim of this study is to measure the extent of out-of-pocket funding of healthcare services by the older adult population. The study has three objectives: to profile the healthcare services for which older adults pay out of pocket, profile the older adults who pay out of pocket for medical services and detect changes over the years, and identify predictors of out-of-pocket healthcare services funding by older adults. The study is predicated on the SHARE-Israel database (SHARE—Survey of Health, Ageing and Retirement in Europe). Relating to information yielded by the last two waves of SHARE-Israel (Wave 7 and Wave 8), it sheds light on the characteristics of those who reported having paid out-of-pocket for medical services. A large majority of the older-adult population in Israel that consumes healthcare services is asked to pay for services out of pocket. Having supplemental health insurance, personal state of health and changes in it, and economic resources are found to have the strongest effect on the probability of out-of-pocket funding. The motive of financial and/or social support that older adults receive from and/or give to their immediate surroundings makes it more likely that they will pay out of pocket for healthcare services. The probability of such funding varies between nationalities and immigration statuses. It is found with emphasis that the share of out-of-pocket funding of healthcare in older adult households’ total annual income is trending upward. Furthermore, economic motives are central in determining whether such expenditure will stabilize over time. The findings stress the need to enhance the healthcare system’s awareness of the profile of older adults who find it necessary to pay out of pocket for healthcare services.